"I always feel like somebody's watching me" - Rachel Gibson; Esmeralda Bon; Kathryn Dommett (Journal of Quantitative Description: Digital Media)
The practice of political micro-targeting (PMT) – tailoring messages for voters based on their personal data – has increased over the past two decades, particularly in the U.S. Studies of PMT have to date concentrated largely on its effects on voters, or its implications for democracy more broadly. Less attention has been given to answering basic descriptive questions about how people perceive, feel and care about this new mode of political communication. This paper fills that gap by reporting findings from an online survey (weighted to be nationally representative on age, gender, ethnicity, region and past vote) that measured public attitudes toward PMT during the 2020 U.S. Presidential campaign. Specifically, we measure voter orientations toward PMT in four key dimensions – awareness, aversion, knowledge, and acceptability at the aggregate level – and explore how these vary according to a range of individual characteristics. Key findings are that public understanding and acceptance of PMT may be higher than current studies indicate, particularly among certain sectors of the population. Such insights are important for academic research to cognize and also policy-makers, as they move toward greater regulation of voter targeting.